Analysis of high-order Laguerre-Gaussian laser mode for coupling in microstructured fibers - Bañas, Andrew Rafael M. (Quezon City College of Science, University of the Philippines, 2009)
We analyze the propagation of higher order laser modes through a microstructured fiber. We maximize the throughput of such optical fibers by tailoring the modes of the beam coupled into it. Here, the modes we coupled are the higher order Laguerre-Gaussian (LG) modes. For analysis, we used the finite difference time domain (FDTD) method modified to exploit harmonic behaviour of guided modes in microstructured fibers. With high numerical apertures (NA), increase in coupling efficiencies can be observed when LG modes are coupled instead of the more common TEM00 mode. To lessen the computing overhead in our FDTD analysis, we formulate novel absorbing boundary conditions (ABCs) based on redirecting Ponyting vectors and applying Gauss's law. Our ABCs are much simpler than standard perfectly matched layers ABCs. For the small trade off in reflection error our novel ABCs can make an FDTD simulation up to three times faster as compared to FDTD simulations using perfectly matched layer type ABCs.
Thesis (M.S. Physics)--University of the Philippines Diliman
Keywords: Optical fibers; Magnetic couplings